Hydraulic Characteristics of Axial Flow Pump Device With Different Guide Vane Inlet Angles - Xu, Lei; Zhang, Hucheng; Wang, Chuan; Ji, Dongtao; Shi, Wei; Lu, Weigang; Lu, Linguang (Frontiers in Energy Research, 2022)
To improve the efficiency of low-head pump device in the large-discharge and low-head domain, the hydraulic characteristics of vertical axial flow pump devices with different guide vane inlet angles were studied using computational fluid dynamics (CFD) and model test methods. The and curves of the pump device were obtained for different impeller blade angles when the inlet angle adjustments of the guide vane were 0° and −12°. The resulting hydraulic performance was compared and analyzed. The results showed that the pump device efficiency under low-head and large-discharge conditions was improved when the guide vane inlet angle was rotated in the clockwise direction. The reason for the increased pump device efficiency was analyzed using CFD. When the guide vane inlet angle adjustments were 0° and −12° under low-head working conditions, the vortex in the guide vane was eliminated, the hydraulic loss of the guide vane decreased, and the energy performance of the pump improved. When the operational conditions of the pump device deviate from its high-efficiency zone due to limitations in the pump model or the motor itself, the application of these results could improve its hydraulic performance, which is of great significance to the design and application of low-head pump devices.